2009
DOI: 10.1107/s1600536809038665
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-3-(9-Anthryl)-1-(4-methoxyphenyl)prop-2-en-1-one

Abstract: This paper is dedicated to the late His Royal Highness Prince Mahidol of Songkla for his contributions to the development of medical education in Thailand on the occasion of Mahidol Day which falls on the 24th September.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The dihedral angles between the mean planes of the 2-anthryl and benzene rings are 73.0 (9)° and 73.3 (3)° in A and B, respectively. Bond lengths and angles are normal and correspond to those observed in the related compounds ((Z)-3-(9-anthryl)-1-(4-methoxyphenyl) prop-2-en-1-one (Chantrapromma et al, 2009), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one (Suwunwong et al, 2009), (Z)-3-(9-anthryl)-1-(4-bromophenyl)-2-(4-nitro-1H-imidazol-1-yl) prop-2-en-1-one (Lu et al, 2009), (Z)-3-(9-anthryl)-2-(4-nitro-1H-imidazol-1-yl)-1-p-tolylprop-2-en-1-one (Wang et al, 2009) and (E)-3-(9anthryl)-1-(4-fluorophenyl)-2-(4-nitro-1H-imidazol-1-yl) prop-2-en-1-one (Wang et al, 2010).…”
Section: Data Collectionsupporting
confidence: 66%
See 1 more Smart Citation
“…The dihedral angles between the mean planes of the 2-anthryl and benzene rings are 73.0 (9)° and 73.3 (3)° in A and B, respectively. Bond lengths and angles are normal and correspond to those observed in the related compounds ((Z)-3-(9-anthryl)-1-(4-methoxyphenyl) prop-2-en-1-one (Chantrapromma et al, 2009), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one (Suwunwong et al, 2009), (Z)-3-(9-anthryl)-1-(4-bromophenyl)-2-(4-nitro-1H-imidazol-1-yl) prop-2-en-1-one (Lu et al, 2009), (Z)-3-(9-anthryl)-2-(4-nitro-1H-imidazol-1-yl)-1-p-tolylprop-2-en-1-one (Wang et al, 2009) and (E)-3-(9anthryl)-1-(4-fluorophenyl)-2-(4-nitro-1H-imidazol-1-yl) prop-2-en-1-one (Wang et al, 2010).…”
Section: Data Collectionsupporting
confidence: 66%
“…For related structures, see: Chantrapromma et al (2009); Jasinski et al (2010Jasinski et al ( , 2011a; Lu et al (2009); ; Wang et al (2009Wang et al ( , 2010.…”
Section: Related Literaturementioning
confidence: 99%
“…For a related structure and background references to chalcones, see: Fun et al (2010). For related structures, see: Chantrapromma et al (2009Chantrapromma et al ( , 2010; Fun et al (2009); Horkaew et al (2010); Lu et al (2009); ; Wang et al (2009Wang et al ( , 2010; Jasinski et al (2011). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…In continuation of our studies on the crystal structures of chalcones (Fun et al, 2010), we now report the synthesis and crystal structure of the title compound, (I). The structures of some related chalcones viz: (Z)-3-(9-anthryl)-1-(4-methoxyphenyl)prop-2-en-1-one (Chantrapromma et al, 2009), (Z)-3-(9-anthryl)-1-(2-thienyl)prop-2-en-1-one (Fun et al, 2009), (E)-3-(anthracen-9-yl)-1-(4-bromophenyl)prop-2-en-1-one , (Z)-3-(9-anthryl)-1-(4-bromophenyl)-2-(4-nitro-1H-imidazol-1-yl)prop-2-en-1-one (Lu et al, 2009) (Horkaew et al, 2010), and an orthorhombic polymorph of (Z)-3-(9-anthryl)-1-(2-thienyl)prop-2-en-1-one (Chantrapromma et al, 2010) and 2(E)-3-(4hydroxyphenyl)-1-(4-chlorophenyl) prop-2-en-1-one (Jasinski et al,2011) have been reported.…”
Section: S1 Commentmentioning
confidence: 99%
“…For bond-length data, see: Allen et al (1987). For related structures, see: Chantrapromma et al (2009Chantrapromma et al ( , 2010; Suwunwong et al (2009). For background to and applications of chalcones, see: Kobkeatthawin et al (2010); Nowakowska (2007); Oliveira et al (2007); Patil & Dharmaprakash (2008); Saydam et al (2003); Svetlichny et al (2007); Tewtrakul et al (2003).…”
Section: Related Literaturementioning
confidence: 99%